2016
DOI: 10.1140/epjc/s10052-016-4288-1
|View full text |Cite
|
Sign up to set email alerts
|

Static spherically symmetric wormholes in f(R, T) gravity

Abstract: In this work, we explore wormhole solutions in f (R, T ) theory of gravity, where R is the scalar curvature and T is the trace of stress-energy tensor of matter. To investigate this, we consider a static spherically symmetric geometry with matter contents as anisotropic, isotropic, and barotropic fluids in three separate cases. By taking into account the Starobinsky f (R) model, we analyze the behavior of energy conditions for these different kinds of fluids. It is shown that the wormhole solutions can be cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(111 citation statements)
references
References 59 publications
2
106
0
Order By: Relevance
“…As regards the matter content of the present WH solutions, we would like to highlight that, departing from what can be found in the f (R, T ) WH literature [22][23][24][25][26][27], no equation of state (EoS) was assumed in this article. Since the WH EoS is still poorly known, this is a considerable advantage of the present solutions.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As regards the matter content of the present WH solutions, we would like to highlight that, departing from what can be found in the f (R, T ) WH literature [22][23][24][25][26][27], no equation of state (EoS) was assumed in this article. Since the WH EoS is still poorly known, this is a considerable advantage of the present solutions.…”
Section: Discussionmentioning
confidence: 85%
“…[22], WHs were firstly analyzed within the linear frame of f (R, T ) gravity, i.e., f (R, T ) = R+2λT , with the matter Lagrangian L m = −ρ, ρ being the matter-energy density of the WH. Static numerical solutions have been obtained for different WH matter contents and stable solutions were attained in [23,24]. Moraes et al have investigated some theoretical predictions for static WHs obtained from f (R, T ) gravity where the matter Lagrangian is governed by the total pressure of the WH [25].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, WEC shows that the matter-energy is always non-negative. In f (R, T ) gravity, the matter support of wormholes is examined by the behavior of energy conditions and the nature of solution for FRW model with perfect fluid matter is studied through energy conditions [65,66]. According to the predefined literature, one can consider the energy conditions to be useful to analyze the behavior of cosmological solutions throughout the universe.…”
Section: Field Equations and Solutionsmentioning
confidence: 99%
“…Lobo and Oliveira [10] investigated WH solutions in f (R) gravity for n = −1/2, 1 with this form of χ(r). Zubair and his collaborators [16] studied static spherically symmetric WH solutions for n = 1/2, 1 and −3 in the background of f (R, T ) gravity. For n = 1/2, Pavlovic and Sossich [22] …”
Section: Anisotropic Fluidmentioning
confidence: 99%
“…We have explored WH geometries for traceless, isotropic as well as barotropic matter distributions and concluded that realistic WH solutions exist in f (G) gravity only for radial barotropic fluid [15]. Zubair and his collaborators [16] investigated WH solutions and found that stable physically acceptable WH solutions exist for anisotropic matter configuration.…”
Section: Introductionmentioning
confidence: 99%